The Influence of Problem Base Instruction Learning Model on Reasoning Ability in Mathematics Learning On the Principle Of The Theorem Discussion Phytagoras in Class Ix Smpn I Rantau Utara - Anggi Ananda Sari Nst; Eva Julyanti (Budapest International Research and Critics University, 2022)
This study aims to determine whether the learning outcomes of students who are taught with the Problem Based Instruction learning model on reasoning abilities in learning mathematics are better than the learning outcomes of students who are taught without the Problem Based Instruction learning model on the subject of the Pythagorean Theorem. The population of this study were all grade IX students of SMP Negeri 1 Rantau Utara. The research sample was taken by random sampling as many as two classes, namely the experimental class and the control class. The experimental class was treated with the Problem Based Instruction learning model for class IX-1, amounting to thirty-two, while the control class was taught using the Conventional model for class IX-3, amounting to thirty-two.The data used are student learning outcomes collected using tests that have been tested for validity, reliability, level of difficulty and differentiating power. The data obtained were analyzed by one-sided t-test after being tested for normality and homogeneity. From the research, the average pretest value for the experimental class was 44.22 and the control was 43.91, while the average post-test value for the experimental class was 79.53 and the control was 65.00. There are pretest and posttest data for each class, then the gain is calculated, by first testing the normality and homogeneity. From the calculation of the average gain, an increase in student learning outcomes was obtained. The results of the calculation on the t-test based on the students' mathematical reasoning ability obtained thit = 8.26 and ttable = 1.699 at the significance a= 0.05 with dk = 62. These data indicate reasoning ability students' mathematics with the PBI learning model is better than the conventional learning model.This means that tcount > ttable, thus Ho is rejected and Ha is accepted. So it can be concluded that the learning outcomes of students who are treated with Problem Based Instruction learning model on reasoning abilities in mathematics learning are better than learning with conventional models on the subject of the Pythagorean Theorem.